The evaluation of biological maturity in sport - Jovanović Jovan (College of Sports and Health, Belgrade, 2019)
The aim of the paper is to present various methods for the evaluation of biological maturity which can define the differences between chronological age and biological maturity in young athletes. Biological maturation is a nonlinear process, taking place at all organic levels, differing from the flow of time after birth. From this point of view, there is a need to determine the differences in the rate of biological maturation within the chronological period. Defining the biological maturity of athletes has a multidimensional significance, the evaluation of youth's maturity in comparison with the chronological age has an implicit value, the selection and prediction of sports achievement at the individual level is crucial for the planning and programming of the training process. Maturity evaluation feedback has a function in preventing and restraining injuries of athletes who are behind their peers. Athletes who are advanced in comparison to their chronological generation, in younger selections, reach a plateau of sports performance early, which can negatively affect success in the senior period. The paper presents the basic methods of evaluation of biological matrices used in the diagnosis of young athletes. Biological maturity can be determined by means of radiography, anthropometric measurements, and sex-based indicators.